Periodismo deportivo y su influencia en las categorías sub 16 y sub 18 de la Institución Deportiva Formativa JS del cantón Quevedo año 2021 - Loor Macias, Doris Maria (2022)
Taking into account that sport is the fundamental basis of good living for people, this research project was born from the lack in the practice of sport. One of the branches of journalism that has a great influence worldwide is undoubtedly sports journalism, since sport has millions of viewers who are aware of the information generated using different media such as television, radio, newspapers. and internet (digital newspapers, social networks) in the different sports disciplines. The purpose we have is to make known what the role of the sports journalist is, whether professional or empirical. Determine what is the influence of the sports journalist in the practice of sport, if they have really contributed to the growth of sport. The importance of making very clear the true role of the communication professional in the sports area so that they do not lose ethics, the impartiality with which they must act and leave their passion for a specific institution and the design of new tools for mass use of sport, where the communicator knows about all sports disciplines to guide and encourage practice.